Oral health of institutionalized elderly: management and primary health care - de Araújo, Isabela Dantas Torres; Nunes, Vilani Medeiros de Araújo; Gama, Zenewton André da Silva; Machado, Flávia Christiane de Azevedo; Sousa, Kelienny de Meneses; Piuvezam, Grasiela (Saúde (Santa Maria), 2020)
Objective: The purpose of this paper was to evaluate the actions developed in oral health directed toward the institutionalized senior population from the perspective of municipal health managers and oral health professionals in primary care in Brazil. Methods: A qualitative, observational, and analytical study was developed and carried out in 11 municipalities between 2008 and 2010. Semi-structured interviews and analysis by ALCESTE software were used. The results from 48 subjects were analyzed. Results: The analysis revealed a 64% and 77% success rate for the corpus of health managers and oral health professionals, respectively. An Ishikawa diagram was generated using the subjects’ responses to identify the quality problem. Conclusions: This study verified that there is a lack of implementation of public policies directed toward seniors and also highlighted that there was lack of incentives and training to assist seniors in the municipalities. Therefore, it is necessary to invest in greater attention for senior patients who reside in homes for the aged.